Implementation of Artificial Intelligence in Public Services: Analysis of Readiness and Adaptation Strategies of The Indonesian Bureaucracy - Suparno Suparno; Emiliana Sri Pudjiarti (International Journal of Humanities and Social Sciences Reviews, 2026)
Digital transformation through Artificial Intelligence (AI) is imperative for public services, but its implementation in Indonesia faces various challenges. This study analyses the readiness level of the Indonesian bureaucracy and the role of adaptation strategies as a mediating mechanism for successful AI implementation. Using explanatory sequential mixed methods, the study involved 287 respondents from 68 government agencies using PLS-SEM analysis, followed by in-depth interviews with 33 informants from 11 agencies for qualitative exploration. The results indicate that the readiness of the Indonesian bureaucracy is in the moderate category, with human resource readiness as the most critical weakness. PLS analysis confirmed that all readiness dimensions significantly influence adaptation strategies, with human resource readiness as the strongest predictor. Adaptation strategies partially mediated the readiness-implementation relationship, explaining 70.4% of the variance in AI implementation. Qualitative findings identified effective strategies: phased pilot projects, change management through champions, continuous capacity building, incremental implementation, and adaptive governance. Structural barriers include rigid regulations, silo mentality, and political turnover. The study produced the ARSI Framework as a practical guide for AI implementation in the Indonesian public sector, emphasising the importance of strategic execution in translating readiness into successful implementation.